The impact of family residence structure on adolescents’ non-cognitive abilities: evidence from China - Tang, Bin; Xiao, Siyi; Zhang, Yi; Liu, Siyan; Lin, Xiaoli; Liu, Han (Frontiers in Psychology, 2024)
Purpose The family residence structure serves as a crucial pathway through which the family environment influences adolescents’ development. Methods Drawing on nationally representative data, this study employs multiple linear regression models and propensity score matching to examine the impact of various family residence structures on adolescents’ non-cognitive abilities. Causal identification is achieved through propensity score matching, while robustness is assessed using methods such as augmented inverse probability weighting and placebo tests. Heterogeneity analysis is conducted based on gender and household registration, aiming to explore the mechanisms by which family residence structure affects adolescents’ non-cognitive abilities. Results The findings indicate that compared to two-parent co-residence households, three-generation co-residence families have significantly positive effects on emotional stability, conscientiousness, and agreeableness among adolescents. In contrast, skip-generation coresidence families exhibit significant negative effects on emotional stability and agreeableness in adolescents. Further investigation into the underlying mechanisms reveals that parental involvement and family socioeconomic status within three-generation co-residence families positively influence adolescents’ non-cognitive abilities. Conclusion This study highlights the importance of considering grandparents’ role in adolescent growth and advocates for policy recommendations focusing on enhancing non-cognitive abilities in adolescents from skip-generation co-residence families.